Bank bonds: Size, systemic relevance and the sovereign - Andrea Zaghini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
We analyze the risk premium on bank bonds at origination with a special focus on the role of implicit and explicit public guarantees and the systemic relevance of the issuing institutions. By looking at the asset swap spread on 5,500 bonds, we find that explicit guarantees and sovereign creditworthiness have a substantial effect on the risk premium. In addition, while large institutions still enjoy lower issuance costs linked to the TBTF framework, we find evidence of enhanced market disciple for systemically important banks which face, since the onset of the financial crisis, an increased premium on bond placements.
Keywords: G21; G01; G18; 330; Too-big-to-fail; Market discipline; Sovereign guarantees; G-SIFIs